Introduction: the political economy of managerialism. Issue 4 (3rd July 2020) - Eagleton-Pierce, Matthew; Knafo, Samuel
Abstract: As a set of ideas and practices, managerialism has arguably become a powerful behavioural logic shaping a range of processes and outcomes of governance in the world economy. Yet IPE has yet to directly interrogate managerialism as a distinct object of analysis. In this special issue, we bring together a range of authors to explore how managerialism reveals a set of complex histories, agents, and implications that are not self-evident and carry direct relevance for how we understand the global economy. Our main contention is that managerialism is not simply a technical means for the pursuit of policies, but has come to shape the very ways in which policy, and governance more generally, are conceived and conducted. Across a range of cases and fields, we dissect the emergence of the managerial logic, along with how it produces uneven mutations, ruptures, and forms of resistance. In doing so, we reflect upon the requirements for developing a political economy of managerialism.